Targeting gap junctional intercellular communication by hepatocarcinogenic compounds. (17th August 2020) - Leroy, Kaat; Pieters, Alanah; Tabernilla, Andrés; Cooreman, Axelle; Van Campenhout, Raf; Cogliati, Bruno; Vinken, Mathieu
ABSTRACT: Gap junctions in liver, as in other organs, play a critical role in tissue homeostasis. Inherently, these cellular constituents are major targets for systemic toxicity and diseases, including cancer. This review provides an overview of chemicals that compromise liver gap junctions, in particular biological toxins, organic solvents, pesticides, pharmaceuticals, peroxides, metals and phthalates. The focus in this review is placed upon the mechanistic scenarios that underlie these adverse effects. Further, the potential use of gap junctional activity as an in vitro biomarker to identify non-genotoxic hepatocarcinogenic chemicals is discussed.